Penanaman nasionalisme kebangsaan pada siswa SD Muhammadiyah Muntok, Bangka Barat - Arfa Dila; Dinie Anggraeni Dewi (Universitas Negeri Manado, 2021)
The inculcation of nationalism values can be carried out in various ways. The purpose of this study was to determine the implementation of the values of nationalism, constraints, and solutions in the implementation of the value of nationalism in SD Muhammadiyah Muntok. Implementation, obstacles and solutions in this study are the implementation of strengthening the values of nationalism in learning and outside learning activities. This research uses a qualitative approach with descriptive research type. The subjects are class teachers and subject teachers at SD Muhammadiyah Muntok. Collection through direct interviews, questionnaire collection, observation, and documentation. The results showed that SD Muhammadiyah Muntok implements the value of nationalism in and in learning activities. Examples of planting nationalism values include inserting various things and